1975
DOI: 10.4267/2042/65843
|View full text |Cite
|
Sign up to set email alerts
|

Une enzootie de toxoplasmose caprine abortive

Abstract: La technique d’immunofluorescence indirecte a permis d’établir un diagnostic de Toxoplasmose évolutive lors d’une enzootie abortive sévissant dans un troupeau caprin des Alpes-Maritimes. Les résultats sérologiques obtenus démontrent l’intérêt de cette technique pour le dépistage rapide des avortements à Toxoplasmes chez les petits ruminants et pour l’étude épidémiologique de la maladie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In sheep, the disease is clinically evident when more than 5000 parasites are present in the affected animals (Calamel and Giauffret 1976, Rojo Vazquez and others 1981). Scala and others (1991) showed that in sheep with parasite burdens of between 16 and 828 trematodes, the macroscopic lesions were variable and did not correlate with the number of parasites found.…”
Section: Figurementioning
confidence: 99%
“…In sheep, the disease is clinically evident when more than 5000 parasites are present in the affected animals (Calamel and Giauffret 1976, Rojo Vazquez and others 1981). Scala and others (1991) showed that in sheep with parasite burdens of between 16 and 828 trematodes, the macroscopic lesions were variable and did not correlate with the number of parasites found.…”
Section: Figurementioning
confidence: 99%